Firms' motivation for training apprentices : an Australian-German comparison - Pfeifer, Harald [Verfasser] (My University, 2016)
"This paper looks at firms' motivation for training apprentices in both Australia and Germany. The study explores how these countries compare when dealing with their respective institutional arrangements for apprenticeship training. It then analyses Australian employer's commitment to training based on changes to incentive payments in Australia. Overall, the paper finds that institutional frameworks in Germany foster an investment model, a model which emphasises the benefits of employing apprentices after training, while in Australia some firms foster more of a production (that is, substitution for 'regular' workers) model of apprenticeship training, although there is a relatively strong investment motivation for trade firms in Australia." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.1.1 Ausbildungsstellenmarkt; S 4.1 Finanzierungsquellen; I 2.1 Deutschland; I 2.3.5 Australien, Ozeanien; Betriebliche Berufsausbildung; Ausbildungsbereitschaft; Ausbildungsinvestition; Internationaler Vergleich; Bundesrepublik Deutschland; Australien